An Empirical Analysis of Organization Modularization’s Impact – The Case of Google - Liu, Yuanyuan (2017)
Google, as a high-tech internet-based company, is facing a rapidly evolving, intensely competitive environment. So, the company is subject to changing technologies, shifting user needs, and frequent introductions of new products and services. Competing successfully Google relies heavily on the ability to accurately predict and grasp the opportunities of technology developments to launch innovative products or services to the marketplace rapidly. Consequently, under the competitive pressure to innovation, Google must continue to invest significant resources in R&D or get the expertise and skills through acquisitions. In 2015, most of Google’s businesses was operating in one company which led to many troubles in capital market and internal management including business performance evaluation, resources allocation, talents retention, so it was vital for Google to introduce a reasonable organization structure to support the innovation at that time. The purpose of this study was to critically analyze the reorganization of Alphabet Inc. in the year of 2015 to examine the impacts of organization modularization on organization performance. Both qualitative and quantitative research methods are applied to analyze the performance after reorganization, and also the dissertation compares the financial data and management data over time with other internet-based companies such as Facebook, Baidu. The conclusion can be drawn that the period of 2 years is too short to examine the impact of Google’s organization modularization on the organization. But the reorganization in 2015 brings many benefits for Alphabet including the external capital market performance, the internal management improvements. Alphabet’s organization modularization can make businesses more autonomous, and provide the possibility of utilizing the company's resources for emerging but non-profitable projects.